Usability of medication event reminder monitoring system and other determinants to improve the adherence to anti-tuberculosis drugs among patients of tertiary care hospital, Hyderabad - Sudha Bala; B Manoj Aravind; Shashanka Kadas; Harshal Pandve; Sneha Shukla; A Rajesham; Haritha Arnipalli (Wolters Kluwer Medknow Publications, 2023)
INTRODUCTION: Novel strategies to improve the adherence to anti-tuberculosis (TB) drugs include the digital adherence technology for monitoring these patients. The purpose of the study is to determine the acceptability and satisfaction of the medication event reminder monitoring system (MERMS) by the patients and to assess various determinants among adherent and nonadherent groups. MATERIALS AND METHODS: A facility-based cross-sectional study was undertaken among the drug-sensitive TB patients of a TB unit where the MERMS box was issued to them on a pilot basis under the national program. These were assessed on a validated scale of 11 questions graded on a 5-point Likert scale for the usability of MERMS box and various determinants among adherent and Nnonadherent groups were assessed. RESULTS: A total of 126 patients were included in our study with high satisfaction scores for the usage of the MERMS box. There was 89.7% adherence and 10.3% Nonadherence with this and the determinants found to be statistically significant were the large distance of the center from home, loss of daily wages, any of the family problems, Having insufficient money for performing regular investigations, fear of side effects of drugs, social stigma attached, travel cost, long waiting periods at DOTS center, and any toxicity of drugs being experienced. CONCLUSIONS: The usability of MERMS can be enhanced by bringing changes in the font of printed labels and operation instructions and the removal of social stigma can improve adherence.